Effects of transitional care model on postpartum depression of primiparas (产后延续护理对初产妇产后抑郁的影响) - ZHANG Yongqiang (张勇强); YANG Jingying (杨晶莹); LIU Huiling (刘会玲); XU Yuanle (许远乐); ZHU Kunkun (朱坤坤) (中西医结合护理)
Objective To investigate the effect of transitional care model on postpartum depression of primiparas. Methods Totally 400 primiparas were randomly divided in to the control group and observation group, with 200 cases in each group. Primiparas in the control group received routine nursing and health education, and those in the observation group were given transitional care. The Self-rating Anxiety Scale (SAS) and Self-rating Depression Scale (SDS) were used to measure the psychological states. The Pittsburgh Sleep Quality Index (PSQI) was used for sleep quality measurement. The incidence of postpartum depression and satisfaction degree were investigated. Results Scores of SDS and SAS were decreased in both two groups after intervention, and Scores of SDS and SAS in the observation group were lower than those in the control group (P＜0. 01). Score of PSQI was decreased in both two groups after intervention, and score of PSQI in the observation group was lower than that in the control group(P＜0. 01). Compared with those in the control group, A lower incidence of postpartum depression and higher satisfaction degree were reported in the observation, with a significant difference(P＜0. 01). Conclusion The transitional care model, as a proved way of optimizing quality of postpartum nursing, is effective to relieve the primipara’s negative emotion, improve the sleep quality and reduce the incidence of postpartum depression. (目的 探讨产后延续护理对初产妇产后抑郁的影响, 分析优化措施。方法 采用随机数字表法进行分组, 将2019年1月—2022年1月接诊的400例初产妇分为两组: 对照组200例, 提供常规指导; 观察组200例, 提供产后延续护理。采用焦虑自评量表(SAS)和抑郁自评量表(SDS)评价心理状态; 采用匹兹堡睡眠质量指数量表(PSQI)评估睡眠质量; 对比两组产后抑郁发生率、产妇满意度。结果 干预后, 两组SDS和SAS量表评分均较干预前下降, 且观察组SDS、SAS评分低于对照组, 差异有统计学意义(P＜0. 01)。干预后, 两组PSQI评分均较干预前下降, 且观察组PSQI评分低于对照组, 差异有统计学意义(P＜0. 01)。观察组产后抑郁发生率低于对照组(P＜0. 01)。观察组产妇满意度高于对照组(P＜0. 01)。结论 对初产妇实施产后延续护理, 能够改善产妇的负面情绪, 提高睡眠质量, 降低产后抑郁的发生率, 提高产妇的护理满意度, 进一步优化产后延续护理质量。)